Barriers, Benefits, and Enhancers of Employment for Persons with Down Syndrome: An Exploratory Qualitative Study from the Malaysian’s Perspectives - Abg Safuan, Adenan (2023)
Integrating persons with disabilities (PWDs) into society is the most critical issue of the current social policies. Globally, PWDs have a notably higher unemployment rate. Among them, the socio-economic research on persons with Down syndrome (PDS) is scant. No current data on their employment exist, and the reasons for these low employment rates are not understood. To uphold their employment rights, this study aims to explore the employment barriers, benefits, and enhancers for PDS in Malaysia from multiple perspectives. A series of online semi-structured interviews were conducted. Forty-five participants were interviewed: six PDS, ten family members or caregivers, six employers and co-workers, 22 community members, and one policymaker. A reflexive thematic analysis was employed, to generate the themes and subthemes. A thematic map incorporating the three domains of barriers, benefits, and enhancers of employment were generated. For the barriers, the themes generated were: (1) individual circumstances, (2) family concerns, (3) organizational practice, (4) social norms, and (5) restrictive environment. Under the benefits, three themes were constructed: (1) personal growth, (2) employer’s incentives, and (3) improving social acceptance. Finally, for the drivers, the themes include (1) individual strength, (2) family support, (3) inclusive workplace, (4) inclusive community, and (5) supportive environment. Employment for PDS is a complex issue interwoven within every aspect of our social and environmental context. Therefore, securing employment is not only individualistic but demands the willingness of society and the workforce to accommodate them. Relevant authorities, non-governmental organizations (NGOs), and private sectors can utilise the findings to develop better, more inclusive employment policies for PWDs.